The Impact of Social and Economic Changes of Digital Nomadic on Tourists and the Local Community in Canggu - Radha, Ni Luh Radha Kunda; Sunarta, I Nyoman Sunarta; Indra, Gde Indra Bhaskara (International journal of technology and education research, 2024)
This research focuses on the social and economic impacts of digital nomad tourism in Canggu, a popular destination in Bali. Digital nomads, who integrate work and travel, are influencing the local economy and social structure. While tourism theoretically enhances local infrastructure and boosts the economy, the reality in Canggu presents different challenges. The influx of digital nomads has led to economic benefits for some, particularly in sectors like hospitality and services. However, local residents face rising property prices and living costs, creating an uneven distribution of economic advantages. Socially, digital nomad tourism has shifted interpersonal interactions from face-to-face communication to digital platforms, affecting traditional social values and cohesion. Additionally, environmental issues, such as water pollution due to insufficient waste management in local businesses, are emerging concerns. Conflicts between local communities and investors also arise, as some business deals breach initial agreements. The research highlights the need for a more holistic and inclusive approach to digital nomad tourism development in Canggu. This approach should address social, cultural, and economic factors while ensuring that the benefits are distributed more equitably across the local community. Infrastructure improvements must support both digital nomads and local residents while maintaining environmental sustainability. The findings suggest that while digital nomad tourism has potential, its development must be carefully managed to balance economic growth with the social and environmental well-being of Canggu’s local community.